(E)‐3‐(Alkoxycarbonyl‐2‐Alkyliden)‐2‐Oxindoles: Multidentate Pronucleophiles for the Organocatalytic, Vinylogous Michael Addition to Nitroolefins. Issue 4 (12th December 2017) - Curti, Claudio; Battistini, Lucia; Sartori, Andrea; Rassu, Gloria; Pelosi, Giorgio; Lombardo, Marco; Zanardi, Franca
Abstract: We introduce 3‐(alkoxycarbonyl‐2‐alkyliden)‐2‐oxindoles as pronucleophilic donors in the direct, vinylogous Michael addition to nitroolefins orchestrated by a chiral, bifunctional cinchona‐thiourea organocatalyst. This reaction displays excellent levels of γ‐site‐, diastereo‐ and enantioselectivity delivering valuable enantioenriched functionalized oxindoles. Of note, the C‐γ enolization of these pronucleophiles by the organocatalyst generates a multidentate, captodative dienolate that delivers vinylogous adducts with an unprecedented Z ‐selectivity through a peculiar interaction with the catalyst and the nitroolefin. The optimized procedure is operatively simple: the reaction is conducted in air, at room temperature, with low catalyst loading (up to 1 mol%). The synthetic versatility of these Michael adducts is demonstrated by several transformations leading to a valuable quaternary oxindolyl proline analogue and a chiral spirocyclic furoindolone structure. Finally, a mechanistic rationale and a suitable transition state accounting for the observed selectivities are proposed, which are supported by DFT calculations. Abstract :